Sosialisasi Penggunaan Tanaman Herbal Pada Lansia Penderita Hipertensi di Desa Pulo Bandring - Ulfa Nur, Ayu; Mahyunidar; Nurhaliza, Siti; Suhada (Cattleya Darmaya Fortuna, 2023)
Hypertension is a public health problem throughout the world. The Joint Nation Committee on Prevention, Detection, Evaluation, and Treatment on High Blood Pressure VII (JNC VII) stated that almost one billion people suffer from hypertension in the world. Meanwhile, the prevalence of hypertension in Indonesia in 2011 was 31.7% of the population aged 18 years and over. Approximately 80% of hypertension sufferers are classified as essential hypertension. (Azizah, 2011). The elderly will experience various physiological changes due to the aging process, including a decrease in heart capacity which can trigger hypertension. Increasing age causes health to decline little by little. Total cholesterol levels will increase gradually with age. Based on JNC VII, elderly people are said to be hypertensive if systolic blood pressure is > 160 mmHg and diastolic > 100 mmHg. (Kowalski, 2007). Management of hypertension can be carried out using various methods, both pharmacological and non-pharmacological. Pharmacological management of elderly hypertension can be done using modern chemical medicines or herbal treatments. It is necessary to carry out various kinds of interventions in hypertension therapy, including non-pharmacological approaches. Herbal medicine, which is classified as complementary medicine, is a phenomenon that has emerged at this time among the many other non-conventional medicine phenomena, such as treatment with herbs or herbal therapy, acupuncture and cupping. The use of herbs is an alternative treatment that people choose apart from conventional (medical) treatment. (WHO, 2003).